"I believe the findings are fascinating": Stance in three-minute theses. Issue 50 (March 2021) - Hyland, Ken; Zou, Hang (Joanna)
Abstract: Stance, the extent writers intervene in a text to convey their personal attitudes and assessments, has long been a topic of interest to researchers of academic communication. Less studied, however, is how stance functions in spoken discourse. This would seem to be a particularly important issue in the Three Minute Thesis presentation (3MT), a relatively new genre which captures the competitive and high pressure atmosphere of the modern academy. In these competitions doctoral students present their research using only one static slide in just 180s to a panel of judges and non-specialist audience. Using Hyland's (2005a) model, we explore speakers' interactional and evaluative positions in a corpus of 140 3MT presentations from the physical and social sciences. Our findings show that this monologic genre is heavily stance laden and that speakers from the hard and social sciences adopt different stance positions. Hard science students take a stance by casting doubt or asserting certainty in the reliability of information while social scientists claim an authorial self through a more visible personal presence and explicit affective commentary. Our findings have important implications for understanding academic speech genres and for EAP teachers preparing students to orally present their research.